Tuberculosis the Lernaean Hydra of 21st Century - A Post Covid Update on the Indian Scenario: Life Sciences-Public Health - Srinivvasan, T.G.; M, Anita; Bhuminathan, S; Jayesh, Raghavendra; Sruthi, K G (International Journal of Life Science and Pharma Research, 2022)
Tuberculosis is an infectious disease caused by Mycobacterium tuberculosis. Tuberculosis usually affects the lungs, but it can also affect other parts of the body, such as the brain, kidneys, and spine. In most cases, tuberculosis is preventable. However, tuberculosis patients can die if not treated properly. According to the World Health Organization (WHO), tuberculosis (TB) is a worldwide pandemic. It is the primary cause of mortality among HIV-infected individuals. Poor adherence to Tuberculosis treatment can lead to prolonged infection and poor treatment outcomes. Prevention plays a very important role in the fight against TB. Directly Observed Treatment aims to improve adherence to TB treatment by observing patients while they take TB medications. India’s DOTS (directly observed treatment short course) program is the world’s fastest-growing and biggest in terms of patients beginning on treatment, as well as the second-largest in terms of population coverage. Its purpose is to reduce TB mortality and morbidity while also reducing infection transmission until TB is no longer a serious public health concern in India. Multidrug-resistant tuberculosis (MDR-TB) is caused by organisms that are resistant to at least two of the most potent tuberculosis drugs, isoniazid and rifampicin. Multidrug-resistant tuberculosis (MDR-TB) is an increasing danger to tuberculosis eradication, and it is the outcome of a failing tuberculosis control program. Community-based programs can improve patient outcomes by allowing patients to receive treatment at home and addressing socioeconomic barriers to adherence to treatment. This article discusses about Tuberculosis and the ways to manage tuberculosis.